School improvement networks and collaborative inquiry : fostering systemic change in challenging contexts - Pino Yancovic, Mauricio; González Torres, Alvaro; Ahumada Figueroa, Luis; Chapman, Christopher (Emerald professional learning networks series, 2019)
Existing research on Professional Learning Networks looks at experiences in Europe and North America, with very little attention focused on education systems in the Global South, such as Chile. In 2015 more than 500 School Improvement Networks were created to support state-funded schools across the country with the idea of promoting a culture of collaboration. Although schools are expected to work in networks, they are held to account individually through high-stakes standardized testing and external inspections.This book employs the theoretical framework of collaborative inquiry to guide a mixed method study of fifteen in-depth multi-site case studies and descriptive statistical analysis of a questionnaire answered by 400 networks. The analysis provides evidence of the depth and spread of the knowledge and collaborative practices of these networks. Linking with the literature on Professional Learning Networks, this study highlights how school improvement networks can support the professional capital of principals and curriculum coordinators. The findings of this study are discussed around the issue of network sustainability, stressing the importance of network leadership and conditions of system infrastructure to mobilize network knowledge to schools, increasing the potential impact of school networks to transform schools' practices. By providing a unique inquiry, into an under researched part of the globe in regards to school networks, this book will prove invaluable for academics and practitioners in the areas of mixed method research, educational leadership and comparative education.